2020
DOI: 10.1039/d0mo00019a
|View full text |Cite
|
Sign up to set email alerts
|

Serial in-solution digestion protocol for mass spectrometry-based glycomics and proteomics analysis

Abstract: A high-throughput & efficient protocol for mass spectrometry-based glycomic and proteomic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…3a-b. Previous LC-MS/MS-based studies have shown that other enzymes targeted to GAGs, such as hyaluronidase and heparan lysase, can be used in tandem to chondroitinase ABC to serially access the proteoglycome [5]. Ongoing studies aim to incorporate these enzymes into MALDI-IMS multienzyme workflows.…”
Section: Methods Optimization For Chondroitin Sulfate Imaging Msmentioning
confidence: 99%
See 1 more Smart Citation
“…3a-b. Previous LC-MS/MS-based studies have shown that other enzymes targeted to GAGs, such as hyaluronidase and heparan lysase, can be used in tandem to chondroitinase ABC to serially access the proteoglycome [5]. Ongoing studies aim to incorporate these enzymes into MALDI-IMS multienzyme workflows.…”
Section: Methods Optimization For Chondroitin Sulfate Imaging Msmentioning
confidence: 99%
“…Enzymatically targeted techniques have been developed recently for multi-omics studies and can analyze tissue glycomics, glycoproteomics, and/or proteomics from a single sample [5][6][7]. These techniques are largely serial LC-MS/MS strategies applied to fresh-frozen tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple protease approaches have already proven their benefit for glycoproteome characterization (86,(462)(463)(464)(465)(466). Even so, these largely rely on canonical proteases like trypsin, chymotrypsin, GluC, and AspN, among others, and some classes of glycosylation, e.g., mucintype O-glycosylation remain impervious to these proteases.…”
Section: Related Developments In Glycoproteomicsmentioning
confidence: 99%
“…Furthermore, glycosites often occur in regions of proteins that can be undersampled with standard proteomic methodologies that rely on trypsin. Multiple protease approaches have already proven their benefit for glycoproteome characterization ( 86 , 460 , 461 , 462 , 463 , 464 ). Even so, these largely rely on canonical proteases like trypsin, chymotrypsin, GluC, and AspN, among others.…”
Section: Related Developments In Glycoproteomicsmentioning
confidence: 99%
“…Also, the ability to sequence GAG chains should provide critical insight into structure-function relationships. Progress in mass spectrometry-based glycomics in the past decades has been exciting with the aid of bioinformatics (Ricard-Blum and Lisacek, 2017 ; Sethi et al, 2020 ). Ultimately, glycosamino-glycomics would require the capability of unbiased sequencing of any oligosaccharides derived preferentially from the natural source.…”
mentioning
confidence: 99%